Improving the Quality of Islamic Education Learning by Using Learning Video Media at SD Negeri Kain Golong - Siti Hafsah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the quality of Islamic Religious Education learning on the subject of humble attitude by using learning video media in class IV of SDN Kain Golong, Aceh Singkil. This study is a classroom action research that uses four steps, namely planning, action, observation, and reflection. The subjects of this study were 25 fourth grade students and an Islamic Religious Education subject teacher. The data for this study were obtained using test, observation, and interview techniques. The test was used to measure student learning outcomes before and after the application of learning video media, while observation was used to analyze teacher and student learning activities during the learning process. In addition, interviews were conducted to determine student and teacher responses to the use of video media in learning. The data analysis techniques used in this study were qualitative and quantitative descriptive analysis, which included data reduction, data presentation, and drawing conclusions. The results showed that the use of learning video media can improve students' understanding of the subject of humble attitude, increase learning motivation, and make the learning atmosphere more interesting and interactive. This can be seen from the increase in the percentage of student learning completion from cycle I to cycle II. In cycle I, the percentage of student completion reached 65%, while in cycle II it increased to 88%. In addition, observations show that student activity in the learning process also increased, marked by their involvement in discussions and active participation during learning.